Ganti Rugi Pihak Ekspedisi PT Sinar Multi Terhadap Barang Paket yang Hilang Perspektif Fatwa DSN-MUI 43/DSN-MUI/VIII/2004 Tentang Ganti Rugi: Studi Kasus Tanjung Balai - Melisa Siregar; Sahliah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research analyzes the compensation policy of PT Sinar Multi Regional Operations Tanjung Balai in cases of lost packages, by examining its suitability based on the Fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI) Number 43/DSN/MUI/2024 concerning compensation. This fatwa provides sharia guidance regarding the mechanism and amount of compensation that is fair and does not harm both parties. This research uses an empirical approach and library legal research. The empirical method is an approach to obtaining knowledge or information through direct experience, observation and experimentation. The results of this research are the efforts made by PT. Sinar Multi Regional Operations Tanjung Balai, if consumers ask for compensation for the losses they have suffered, that is through deliberation. This process begins with submitting a claim for compensation accompanied by evidence by the sender to PT. Sinar Multi Regional Operations Tanjung Balai will offer problem resolution by deliberation to the sender regarding the compensation process and submission of the nominal amount to be reimbursed. This deliberation was carried out because the company considered that resolving compensation claims using deliberation was easier and did not require a long time.